Caracterización del manejo agronómico del cultivo de Hordeum vulgare L. En los caseríos de Allauca y Nuevo Progreso en Tayabamba, Pataz. - López Vega, Edwin Waldemar (2017)
The present work of research was carried out with the objective of characterizing the agronomic management of the cultivation of Hordeum vulgare. The hamlets of Allauca (3235 masl) and Nuevo Progreso (3 349 masl) in Tayabamba, Pataz, La Libertad. A survey was applied to a sample of 36 farmers, 24 from Allauca and 12 from Nuevo Progreso, who represent 30% of the farmers' register of each country, obtaining the following results: In the villages of Allauca and New progress the management agronomic analysis of barley cultivation is characterized by doing in traditional form. In both houses the preparation of the land is carried out in the months of January and February making a single cross with plow plow and animal traction, using the system of seeding with own seed of the variety UNA 101 of the previous season; sowing takes place in February and March depending on the weather, no chemical fertilizers are used, no diseases or major diseases and weed control are presented in the manual at 30 and 120 days after sowing, being the most frequent weeds the turnip and the chard. It is harvested in the months of August and September, from 8 to 9 months after sowing. The Allauca hamlet, in contrast to the New Progress settlement, has lower slope soils, which determines that 42% of the barley is irrigated by gravity, using more seed (130 and 117 kg Ha -1), the barley is sown in rotation with Dad, there is a greater availability of manure to fertilize the crop (33% and 17% of the producers, respectively) at a higher dose (2 t ha-1 and 1.5 t ha -1, respectively ), showed a higher yield (2,610 kg ha -1 and 2,010 kg ha -1, respectively) and part of the production was destined to the market (12% with respect to 0% en Nuevo Progreso) at an average price of 18 soles per arroba .